The Ecological Conversion of Laudato si' - Quispe López, Ciro (2018)
In recent decades, a new kind of poor has emerged among us. A new poor because of our biased and mistaken actions. A new sort of poor whom we paradoxically label as mother earth and sister earth. The main cause is hidden behind deteriorated relationships, between humans and nature. In the same way the poor claim nowadays for justice, mother earth claims and cries for a better treatment. We are irrationally wearing away all mother’s earth resources, but she will not become the only affected one. This situation involves any of us and we will perceive it just as the poorest are already being affected by it. Therefore, it is compelling to reconstruct the foundations of a new anthropology, led by the principles of a deep and sincere ‘ecological conversion’ and an ‘ecological spirituality’. This new mystique should spread abroad in such a way we rethink not only the traditional paradigms such as progress, development, economy, and peace, but also rethink our compromise with the planet. Only in this way, we can raise a new human who bears in mind his neighbor and nature. The encyclical of Pope Francis (2015), Laudato si', proposes the bases, or rather, the «ecological virtues» for this new human anthropology of which further generations should be part of.